Hypoxic pulmonary endothelial cells release epidermal growth factor leading to vascular smooth muscle cell arginase‐2 expression and proliferation. Issue 11 (8th June 2022) - Chen, Bernadette; Jin, Yi; Pool, Caitlyn M.; Liu, Yusen; Nelin, Leif D.
Abstract: The hallmark of pulmonary hypertension (PH) is vascular remodeling. We have previously shown that human pulmonary microvascular endothelial cells (hPMVEC) respond to hypoxia with epidermal growth factor (EGF) mediated activation of the receptor tyrosine kinase, EGF receptor (EGFR), resulting in arginase‐2 (Arg2)‐dependent proliferation. We hypothesized that the release of EGF by hPMVEC could result in the proliferation of human pulmonary arterial smooth muscle cells (hPASMC) via activation of EGFR on the hPASMC leading to Arg2 up‐regulation. To test this hypothesis, we used conditioned media (CM) from hPMVEC grown either in normoxia (NCM) or hypoxia (HCM). Human PASMC were incubated in normoxia with either HCM or NCM, and HCM caused significant induction of Arg2 and viable cell numbers. When HCM was generated with either an EGF‐neutralizing antibody or an EGFR blocking antibody the resulting HCM did not induce Arg2 or increase viable cell numbers in hPASMC. Adding an EGFR blocking antibody to HCM, prevented the HCM‐induced increase in Arg2 and viable cell numbers. HCM induced robust phosphorylation of hPASMC EGFR. When hPASMC were transfected with siRNA against EGFR the HCM‐induced increase in viable cell numbers was prevented. When hPASMC were treated with the arginase antagonist nor‐NOHA, the HCM‐induced increase in viable cell numbers was prevented. These data suggest that hypoxic hPMVEC releases EGF, which activates hPASMC EGFR leading to Arg2 protein expression and an increase in viable cell numbers. We speculate that EGF neutralizing antibodies or EGFR blocking antibodies represent potential therapeutics to prevent and/or attenuate vascular remodeling in PH associated with hypoxia. Abstract : We hypothesized that the release of epidermal growth factor (EGF) by human pulmonary microvascular endothelial cells (hPMVEC) could result in the proliferation of human pulmonary arterial smooth muscle cells via activation of the EGF receptor (EGFR) on the hPASMC leading to Arg2 up‐regulation. Our data suggest that hypoxic hPMVEC do release EGF, which activates hPASMC EGFR leading to Arg2 protein expression and an increase in viable smooth muscle cell numbers.